2013
DOI: 10.1111/josh.12112
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence: Data Documenting Parental Support for Earlier Sexuality Education

Abstract: Results add substantial support for age-appropriate school-based sexuality education starting at the elementary school level, the new National Sexuality Education Standards, and funding to support evidence-based abstinence-plus or comprehensive sexuality education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 17 publications
2
41
0
3
Order By: Relevance
“…This study adds to the existing evidence that parents are supportive of sexuality education being taught in schools (Barr et al, 2014;Bleakley et al, 2010;Constantine et al, 2007;Dake et al, 2014;Eisenberg et al, 2008;Ito et al, 2006;Kaiser Family Foundation, 2000;Tortolero et al, 2011). Slightly more than 9 out of 10 (92%) parents surveyed in this study showed support for sexuality education to be taught in schools.…”
Section: Sexuality Education Taught In Schoolssupporting
confidence: 54%
See 2 more Smart Citations
“…This study adds to the existing evidence that parents are supportive of sexuality education being taught in schools (Barr et al, 2014;Bleakley et al, 2010;Constantine et al, 2007;Dake et al, 2014;Eisenberg et al, 2008;Ito et al, 2006;Kaiser Family Foundation, 2000;Tortolero et al, 2011). Slightly more than 9 out of 10 (92%) parents surveyed in this study showed support for sexuality education to be taught in schools.…”
Section: Sexuality Education Taught In Schoolssupporting
confidence: 54%
“…Several (66%) of these studies has a specific item that asked parents when sexuality education should begin being taught in schools. In all of those studies parents indicated that the sexuality education topics should be taught in middle school or earlier (Barr et al, 2014;Dake et al, 2014;Eisenberg et al, 2008;Ito et al, 2006;Jordan, Price, & Fitzgerald, 2000;Tortolero et al, 2011).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…South Carolina is generally perceived as a conservative state. However, these findings are consistent with previous research in the state and the nation that indicated high levels of parental and community support for comprehensive approaches to sexual and reproductive health education (Alton, Valois, Oldendick, & Drane, 2009;Barr, Moore, Johnson, Forrest, & Jordan, 2014;Dunn, Thompson, M'Cormack, Yannessa, & Duffy, 2014;Eisenberg et al, 2008;Ito et al, 2006;Rose, Prince, Flynn, Kershner, & Taylor, 2014). These findings are consistent with previous literature that indicated parental support for comprehensive sexuality education as a factor in the adoption of programs and policies (Eisenberg et al, 2008;Ito et al, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…En este sentido, las actitudes evasivas o el silencio también son una forma de transmitir información sobre sexualidad mediante mensajes de censura o prohibición. 2,3 Por otro lado, los medios de comunicación tienen un impacto importante en su desarrollo sexual de los menores de edad, ya que hoy en día se encuentran expuestos (cada vez a menor edad) a manifestaciones erróneas, distorsionadas e incomprensibles de la sexualidad. Existe una gran facilidad para leer contenidos inapropiados y, además, la supervisión de las actividades en internet por parte de los progenitores suele ser insuficiente.…”
Section: Introductionunclassified